2006
DOI: 10.1038/sj.gene.6364322
|View full text |Cite
|
Sign up to set email alerts
|

A network-based analysis of allergen-challenged CD4+ T cells from patients with allergic rhinitis

Abstract: We performed a network-based analysis of DNA microarray data from allergen-challenged CD4 þ T cells from patients with seasonal allergic rhinitis. Differentially expressed genes were organized into a functionally annotated network using the Ingenuity Knowledge Database, which is based on manual review of more than 200 000 publications. The main function of this network is the regulation of lymphocyte apoptosis, a role associated with several genes of the tuber necrosis factor superfamily. The expression of TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 33 publications
(57 reference statements)
1
31
0
Order By: Relevance
“…Several of these genes and pathways have a previously described role in AA pathogenesis, validating that our experimental approach is sufficiently sensitive to capture disease-relevant processes. 10,33 Although it has been shown that NK cells aggregate perifollicularly in AA lesional skin 3,4,34 and peripheral blood, 35,36 there is limited data regarding the role of NK cells in AA pathogenesis. Our data show an upregulation of NK-cell cytotoxicity in AA peripheral blood that, as suggested by others, 11,12,37 may promote the failure of hair follicle immune privilege.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these genes and pathways have a previously described role in AA pathogenesis, validating that our experimental approach is sufficiently sensitive to capture disease-relevant processes. 10,33 Although it has been shown that NK cells aggregate perifollicularly in AA lesional skin 3,4,34 and peripheral blood, 35,36 there is limited data regarding the role of NK cells in AA pathogenesis. Our data show an upregulation of NK-cell cytotoxicity in AA peripheral blood that, as suggested by others, 11,12,37 may promote the failure of hair follicle immune privilege.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in most complex diseases, in SAR it is possible to mimic the disease process by obtaining CD4+ T cells outside of the pollen season, when the patients are asymptomatic, and challenge in vitro with pollen or diluent. Thus, it is possible to identify disease-specific changes by comparing expression differences from allergen-and diluent-challenged cells from patients with those observed in controls (Benson et al 2006a;Bosco et al 2009). This comparison will henceforth be referred to as a delta-delta (ΔΔ) expression analysis.…”
Section: Results Mirnas Regulate Disease-relevant Mrna Modules In Hummentioning
confidence: 99%
“…Paired samples were generated by culturing the CD4+ T cells with allergen or diluent according to the method previously described (Benson et al 2006a). We performed miRNA-and mRNAexpression profiling using Illumina's Human v2 miRNA panel and HumanWG-6 v3.0 Expression BeadChips (Illumina), respectively, on the allergen-and diluent-challenged samples derived from all the 40 subjects, according to the manufacturer's instructions.…”
Section: Mirna-and Gene-expression Profilingmentioning
confidence: 99%
“…Interestingly, in our study we found the TNFRSF17 gene of the same superfamily to be up-regulated most strongly of all immunologic genes (Table 1). Although both studies differ: (a) one is a study into respiratory allergy, the other study is that of a food allergic model; (b) different species were studied; and, (c) Benson et al (2006) studied allergen-specific T-lymphocytes, whereas we studied a pool of MLN cells. With both studies in mind, one could further substantiate the claim that the proliferation of allergen-challenged T H 2 cells is associated with an increase in TNFRSF-family signaling.…”
Section: Discussion and Conlusionsmentioning
confidence: 99%
“…However, microarray data of respiratory allergy studies are available. Benson et al (2006) performed a network-based analysis of DNA microarray data from allergen-challenged CD4 + T-lymphocytes from patients with seasonal allergic rhinitis. They found a strong upregulation of expression of TNFRSF4, one of the genes of the TNF superfamily, which is involved in regulation of apoptosis and T H 2 proliferation.…”
Section: Discussion and Conlusionsmentioning
confidence: 99%